TATA KELOLA PERBANKAN SYARIAH YANG BERKELANJUTAN: ANALISIS TERHADAP KESATBILAN EKONOMI BERDASARKAN PRINSIP SYARIAH (Menelusuri Dampak Positif Tata Kelola Perbankan Syariah terhadap Stabilitas Ekonomi Global dan Penerapannya) - Agus Suryono (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
This study delves into the dynamics of sustainability in Islamic banking governance and its pivotal role in ensuring economic stability through Sharia-based principles. It confronts the challenge of economic instability amid global financial crises and seeks viable solutions within the framework of Sharia-compliant banking practices. Employing a mixed-method methodology, the research involves a quantitative analysis of financial indicators and a qualitative exploration via in-depth interviews with key stakeholders in the industry. The primary goal is to discern the correlation between Sharia-guided banking governance and economic stability, investigating how adherence to these principles fosters sustainable financial systems. The findings of this research reveal a strong and positive relationship between the robust application of Sharia principles in banking governance and the maintenance of economic stability, particularly during tumultuous financial periods. The implications underscore the ethical, inclusive, and stable nature of Sharia-compliant banking, advocating for its broader adoption within the global financial landscape. In conclusion, this study emphasizes the significance of Sharia-compliant banking practices as a catalyst for fostering economic stability and ethical financial systems, providing a potential model for wider integration and sustainability in the broader economy. This study examines the sustainability of Islamic banking governance and its role in ensuring economic stability through Sharia-based principles.